A burocracia segundo Hannah Arendt - Rocha, Lara França da (2025)
The examination of the totalitarian phenomenon prompted political theorist Hannah Arendt to analyse the predicatives that made the systematisation of extermination possible. This investigation demonstrated the disastrous location of bureaucracy in the totalitarian enterprise and, furthermore, proved its continuity even after the end of the total regimes. This permanence helps us to understand the frequency with which bureaucracy appears in Arendt’s theoretical endeavours, sometimes described as a social form of government, as in The Human Condition, sometimes as a symptom of the decline of the nation-state, as in his Philosophical Diary, or even as a tyranny without a tyrant, as in Thinking without banisters. What these different and complementary readings have in common is the observation that it is an anti-political form of government based on the non-participation of the majority of men and women in government decision-making processes, restricted to a minority with the necessary expertise. Considering these tensions, the aim of this thesis is to examine bureaucracy as a form of government based on Hannah Arendt’s political theory, which also implies examining how it makes politics unviable as participation, deliberation, responsibility and freedom. To achieve this, it is first necessary to examine the place of bureaucracy in Arendt’s reflections on forms of governing, as well as the elements that make it possible, such as the rise of society and, with it, of administration and the scientific mentality in politics, the decline of the nation-state and party bureaucracy, inextricably linked to government bureaucracy. Next, based on Arendt’s reading of some characters, the attributes and reverberations of this form of domination will be presented: with Lord Cromer, the historical and political panorama of the emergence of bureaucracy at the end of the 19th century is exposed; with Kafka’s K.’s, the dehumanizing face of bureaucratic domination in the first decades of the 20th century is revealed; while with Eichmann, the characteristics of totalitarian bureaucracies are examined. Finally, with today’s scientifically minded advisors (decision-makers, problem-solvers and image-makers), it is retraced how bureaucracy gained new momentum and demonstrated its crucial adaptability after the end of totalitarian regimes, culminating in digital bureaucracy (e-bureaucracy) and the use of algorithms.